Analysis of the Impact of Turn Signal Usage at Roundabouts on CO Emissions and Traffic Flows - Monika Ziemska-Osuch; Dawid Osuch (Energies)
In contemporary times, one of the challenges in road traffic is the failure of drivers to adhere to traffic regulations. While the use of turn signals may seem trivial, the studies presented in this article demonstrate the significant impact that this practice can have on road traffic, both in terms of urban network capacity and fuel consumption, which consequently affects the emission of exhaust gases into the natural environment. A common example of the failure to use turn signals is when drivers navigate roundabouts. The example presented here analyzes an existing road network configuration consisting of two roundabouts and an intersection between them. The method of microsimulation was employed using the PTV Vissim 25 software. This study examined a scenario where the percentage of drivers adhering to the use of turn signals increased by 10% in each successive simulation version. The results clearly indicate that the capacity of the network, as well as the emissions of road pollutants, depend not only on traffic volume but also, most importantly, on traffic flow efficiency.